Advising the traveller. (January 2018) - Herman, Joanna; Patel, Dipti
Abstract: Global travel continues to increase, particularly to tropical destinations that have different health risks from those encountered closer to home. Currently, over a billion people travel annually, with over 65 million visits made from the UK. Seeking pre-travel advice should be an essential part of any trip for a traveller. The key elements of pre-travel advice are health risk assessment, health promotion and risk management; this involves advice on prevention of malaria, travellers' diarrhoea, sexually transmitted infections and accidents, as well as appropriate vaccinations. Higher risk groups of travellers, such as those visiting friends and relatives, those with co-morbidities, pregnant women and very young or elderly individuals, particularly need to be targeted.